Monetary Value of Live Trade in a Commonly Traded Primate, the Long-Tailed Macaque, Based on Global Trade Statistics - Hansen, Malene Friis; Gill, Mike; Briefer, Elodie Floriane; Nielsen, Daniel R. K.; Nijman, Vincent (Frontiers in Conservation Science, 2022)
Non-human primates (primates) are regarded as key research subjects for pre-clinical trials of several drugs aimed to alleviate human suffering. It has long been suggested, that the predominant species in the international trade in live primates for use in research is the long-tailed macaque Macaca fascicularis. However, little is still known about the value of this international trade apart from anecdotal reports. Whilst the international trade to supply the requirement for biomedical testing is known to encourage illegal wildlife trade we lack detailed understanding of the overall value and magnitude of this trade. This information is vital to facilitate the design of effective conservation strategies in range countries to mitigate the exploitation of wild populations by the organised crime networks. Here, data from CITES and the UN Comtrade databases were combined to calculate the value of this trade. We also compared the individual primates reported traded in the two databases to investigate possible correlations. Results show from 2010 - 2019, the international trade in long-tailed macaques constituted a market worth of ~US $1.25 billion. We found a positive correlation between individual primates traded in the UN Comtrade and individual long-tailed macaques reported in the CITES Trade Database, suggesting that we can use the UN Comtrade to investigate values and magnitude of the international legal trade in wildlife, and that legal trade in live primates is primarily constituted of long-tailed macaques alone.